Mechanical failure and its management in dental implants: A review - Bhochhibhoya, Amar; Shrestha, Rejina (Journal of Orofacial Research, 2022)
Dental implant is one of the most accepted treatment modalities for the replacement of missing teeth. Although the overall success is high, dental implants occasionally fail due to biological, technical, and esthetic reasons. Technical or mechanical complications occur when the strength of materials is not able to resist the forces that are being applied. This may occur due to poor framework design, undue force factors, sub-optimal implant position, and wrong choice of the prosthetic materials. Mechanical complications include fracture of veneers, loss of the screw access hole restoration, abutment screw loosening, abutment screw fracture, fracture of implants, and overdenture clip/attachment fracture. Prompt management of such complications is the key to implant success.